PFM.09 Reduced glutamate: choline ratio by 1H MRS as a Biomarker for Placental Insufficiency in the Growth Restricted Fetus. (9th June 2014) - MacMaught, G; Semple, S; Gray, C; Simpson, M; Norman, JE; Walker, J; Denison, FC
Abstract : Background: Current diagnostic tests for uteroplacental insufficiency are limited. Glutamine and glutamate (Glx) play a vital role in the production of the nucleotides and amino sugars required for cell proliferation in the placenta. Choline (Cho) is a marker of cell turn-over. Proton spectroscopy magnetic resonance spectroscopy ( 1 H MRS) is a safe, non-invasive imaging technique which can detect Glx and Cho. We hypothesised that placenta Glx:Cho ratio could be a useful biomarker of placental function in pregnancies complicated by FGR. Objective: To undertake a proof-of-concept study assessing placental Glx:Cho ratio in women with healthy pregnancies compared to suspected FGR. Study design: In vivo placental 1 H MRS was performed in 7 pregnancies with FGR and matched to healthy controls. MRI placental volumes were measured. Oxygenation and acid-base balance were determined at birth where possible. Results: Figure 1 demonstrates an exemplar spectra. The Glx:Cho ratios are shown in Table 1 . In each case the Glx/Cho ratio for the FGR placentas are lower than in that of their matched control (p < 0.003). Conclusion: This preliminary study demonstrates that Glx/Cho ratio may be a potential biomarker of placental insufficiency. Future studies need to establish normal ranges for gestation and explore the clinical implication of a low Glx/Cho ratio for perinatal outcome.